The Role of Provincial Museums in Shaping Collective Memory during Indonesia's New Order Era, 1990-1998 - Atika Kurnia Putri (Mahesa Research Center (PT. Mahesa Global Publishing), 2025)
This article examines the New Order's efforts to shape the identity, character, and collective memory of society through Monas and the Ranggawarsita Museum, which serve as examples for provincial museums. The initiative to establish provincial museums in Indonesia began during the New Order era, reflecting the spirit of national development and stability. These museums were built in the capital of each province, with collections consisting of objects from their respective regions, including fossils, temple ruins, and cultural artefacts from local communities. The main objective of these provincial museums was to foster national identity, character, and collective memory, thereby strengthening the legitimacy of the New Order regime through narratives and displays organised according to museum guidelines. The analysis employs a historical method that encompasses four stages, incorporating heuristics that involve examining archival data, newspapers, literature studies, and observations of museum displays. Criticism is expressed by comparing the collected data with contemporary information. Interpretation and writing are the final stages of the historical method. Provincial museums were a tool for institutionalising the official history compiled by the New Order government. This had implications for the persistence of narratives and displays in provincial museums until the end of the New Order era. Additionally, provincial museums also struggle to innovate in their narratives and displays, leading to limited visits from primary school students.